First Report Of Rose Leaf Blight Caused By Botrytis Cinerea From Jammu And Kashmir (Applied Biological Research, 2012)
Rose (Rosa hybrida), the symbol of beauty and fragrance, is most popular ornamental plant which occupies prominent place in public gardens and private lawns. During June-July 2009 and 2010, blight  of leaves and petals was observed on rose cv. ‘Gala Red’ in Nishat garden, Srinagar, J&K (India). On  leaves, incipient symptoms observed were water-soaked olive sunken areas or blisters that turned into  tan in colour and developed dark margins. Infected petals exhibited water-soaked appearance that  ultimately turned brown or brownish black. Under humid conditions, grayish brown powdery spore  mass was seen on leaves and petals. Isolation on potato dextrose agar from diseased tissues yielded  fungal colonies with a thick creamy white mycelium that produced globose to black oblong grayish  black sclerotia within 12-15 days of inoculation at 20±1oC and measured 4.6 x 3.7 mm (Plate 1).  Conidia were oval, hyaline, aseptate and measured 2.2 x 1.4 µm. The pathogenicity was established by  inoculating healthy rose leaves cv. ‘Gala Red’ with a conidial suspension (4 x 104spore ml-1) using  detached leaf technique. The typical disease symptoms developed within 7-10 days of inoculation.
Keywords: First Report; Rose Leaf; Jammu And Kashmir